Frontiers of Optoelectronics - GONG, Qihuang; ZHANG, Xinliang; LU, Peixiang; SpringerLink (Online service) (Beijing : Higher Education Press : Imprint: Higher Education Press, co-published with Springer.)
Frontiers of Optoelectronics is an international peer-reviewed journal. All articles published in this journal are emphasized to reflect the scientific discovery and technology innovation in the fields of photonics or optoelectronics. The topics include, but are not limited to, semiconductor optoelectronics, nano-photonics, information photonics, energy photonics, ultrafast photonics, biomedical photonics, nonlinear photonics, fiber optics, laser and terahertz technology and intelligent photonics. The journal publishes reviews, research articles, letters, comments, special issues and so on.
Keywords: Electrical engineering; Physics; Astronomy; Biomedical engineering; Electrical and Electronic Engineering; Physics and Astronomy; Biomedical Engineering and Bioengineering